2013
DOI: 10.5114/aoms.2013.39789
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil apoptosis: impact of granulocyte macrophage colony stimulating factor on cell survival and viability in chronic kidney disease and hemodialysis patients

Abstract: IntroductionAltered neutrophil apoptosis might be responsible for recurrent bacterial infections encountered in hemodialysis (HD) and chronic kidney disease (CKD) patients. This work was designed to assess the neutrophil apoptotic activity and the impact of implementation of granulocyte macrophage colony stimulating factor (GM-CSF), as a survival factor, on neutrophil apoptosis among these patients.Material and methodsTwenty-five patients on regular HD along with 34 CKD patients on conservative treatment, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…The balance between the pro-and anti-apoptotic members of this family is the central factor in the opening and closing of permeability transition pores [6] which is a critical pathway for cytochrome c release from mitochondria and causes apoptosis by activating caspase-9 [7].…”
Section: Introductionmentioning
confidence: 99%
“…The balance between the pro-and anti-apoptotic members of this family is the central factor in the opening and closing of permeability transition pores [6] which is a critical pathway for cytochrome c release from mitochondria and causes apoptosis by activating caspase-9 [7].…”
Section: Introductionmentioning
confidence: 99%
“…GM-CSF regulates inflammation, resistance to viral infections and stimulation of tissue repair [49][50][51]. It stimulates the production of granulocytes and monocyte-macrophages [52].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we showed that 4T1 cells are able to produce s100A8, KC, and GM-CSF that were shown as be able to modulate neutrophil behavior (chemoattraction, survival, functional activation, etc). 72 74 S100A8 is particularly interesting because this molecule is overexpressed in the premetastatic niche 75 where it is produced by myeloid cells and pulmonary epithelium. Then, s100A8 and GM-CSF appeared to be able to stimulate neutrophils to produce IL-16 and could represent a link between 4T1 and neutrophil-derived IL-16 overexpression.…”
Section: Discussionmentioning
confidence: 99%